Transformations of patriarchy in the west : 1500-1900 - Miller, Pavla, 1950- (Bloomington : Indiana University Press, 1998)
"This wide-ranging study of familial, political, and economic change in the West between the sixteenth and the nineteenth centuries is organized around two themes: the rise and fall of a patriarchalist social order and its replacement by fraternal forms of governance; and the attempts by various reformers to instill self-mastery, originally expected of monks and masters, into subject populations, and the frequently unforeseen effects of this process. By linking schooling, state-building, and transformations of patriarchal forms of governance, the book also reopens the debate about the social forces that produced state school systems and about the ways schools affected people and institutions." "Clear and accessible throughout, the book will be of interest to scholars and students in history, sociology, education, women's and gender studies, and cultural studies."--Jacket.
Ch. 1. The Consolidation of Patriarchalism in Early Modern Europe -- Ch. 2. Patriarchalism Challenged -- Ch. 3. Revolutions -- Ch. 4. State Formation, Personality Structure, and the Civilizing Process -- Ch. 5. Worlds of Social Control: Civilizing the Masterless Poor -- Ch. 6. Assembling School Systems -- Ch. 7. Social Movements, Individual Agency, and the School -- Ch. 8. The Reconstruction of Private Life.
Includes bibliographical references (pages 363-388) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Historical sociology; Patriarchy; Social institutions; Social control -- History; Sociologie historique; Patriarcat (Sociologie); Institutions sociales; Contrôle social -- Histoire; historical sociology; social institutions; SOCIAL SCIENCE -- Sociology -- Marriage & Family; Historical sociology; Patriarchy; Social control; Social institutions; Patriarchaat (sociologie); Social Change; Sociology & Social History; Social Sciences; History